Human Brain Lipidomics: Investigation of Formalin Fixed Brains - Beger, Aaron W.; Hauther, Kathleen A.; Dudzik, Beatrix; Woltjer, Randall L.; Wood, Paul L. (Frontiers in Molecular Neuroscience, 2022)
Human brain lipidomics have elucidated structural lipids and lipid signal transduction pathways in neurologic diseases. Such studies have traditionally sourced tissue exclusively from brain bank biorepositories, however, limited inventories signal that these facilities may not be able to keep pace with this growing research domain. Formalin fixed, whole body donors willed to academic institutions offer a potential supplemental tissue source, the lipid profiles of which have yet to be described. To determine the potential of these subjects in lipid analysis, the lipid levels of fresh and fixed frontal cortical grey matter of human donors were compared using high resolution electrospray ionization mass spectrometry. Results revealed commensurate levels of specific triacylglycerols, diacylglycerols, hexosyl ceramides and hydroxy hexosyl ceramides. Baseline levels of these lipid families in human fixed tissue were identified via a broader survey study covering six brain regions: cerebellar grey matter, superior cerebellar peduncle, grey and subcortical white matter of the precentral gyrus, periventricular white matter, and internal capsule. Whole body donors may therefore serve as supplemental tissue sources for lipid analysis in a variety of clinical contexts, including Parkinson’s disease, Alzheimer’s disease, Lewy body dementia, multiple sclerosis and Gaucher’s disease.